2017
DOI: 10.1111/ced.13327
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced haemorrhagic bullous dermatosis

Abstract: The typical clinical course is spontaneous resolution within days to weeks irrespective of continuation of heparin therapy. Because of its self-limiting nature, interruption of heparin therapy may not be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…BHD is sometimes associated with eczematous reaction at sight of injection that may suggest a type IV hypersensitivity reaction [ 32 ]. The propensity for developing lesions on the extremities in older patients also posits local trauma combined with epidermal-dermal fragility as an underlying mechanism [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…BHD is sometimes associated with eczematous reaction at sight of injection that may suggest a type IV hypersensitivity reaction [ 32 ]. The propensity for developing lesions on the extremities in older patients also posits local trauma combined with epidermal-dermal fragility as an underlying mechanism [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin lesions may resolve even if anticoagulation therapy is continued at the same dose. 7,8 Concurrent supportive wound care is beneficial.…”
Section: Photo Challenge Discussionmentioning
confidence: 99%
“…1,2 Bullous hemorrhagic dermatosis is likely underreported, and only 97 cases have been described in peerreviewed journals. 1,[3][4][5][6] The condition has been reported previ-ously in relation to a combination of fonda parinux and warfarin. 7,8 There have been no reported cases associated with direct oral anticoagulants.…”
Section: Probable Fondaparinux-associated Bullous Hemorrhagic Dermatosismentioning
confidence: 99%
“…In a summary of 91 reported cases of bullous hemorrhagic dermatosis, Russo and colleagues found that lesions are not typically painful, pruritic or associated with other systemic symptoms; and lesion distribution is most often distant to injection sites, with primary sites affected being the extremities, followed by the torso, with rare involvement of the mucosal membranes. 1,4 In most cases, bullous hemorrhagic dermatosis is self-resolving, with time to resolution within an average of 13 days. 9 Four deaths have been associated with the condition.…”
Section: Probable Fondaparinux-associated Bullous Hemorrhagic Dermatosismentioning
confidence: 99%